Modern Methods of Linguopoetic Analysis in Uzbek Poetry and Their Educational Significance - Avazova Lobar Buriyevna; Abdusalomova Mavluda Baxrinovna (Scientific Trends, 2025)
This article explores modern methods of linguopoetic analysis in Uzbek poetry, focusing on the integration of linguistic, stylistic, and cultural approaches to interpret poetic texts. The study highlights how contemporary linguopoetic techniques—such as cognitive, semiotic, and discourse analysis—enable a deeper understanding of the aesthetic and emotional dimensions of Uzbek poetic language. The educational significance of these methods is also emphasized, particularly their role in developing students’ linguistic thinking, interpretive skills, and appreciation of national literary heritage. The findings demonstrate that linguopoetic analysis not only enhances literary comprehension but also strengthens cultural and communicative competence in language education.
Keywords: Linguopoetic analysis, Uzbek poetry, cognitive linguistics, stylistics, discourse analysis, education, cultural competence.